Educação do campo: os desafios no trabalho do professor de ciências nas turmas do sistema modular de Ensino Fundamental em Medicilândia-PA - KAPPEL, Camila Fleck (2021)
Rural education has been expanding its scope from social movements that fight for the right to quality education. The municipality of Medicilândia is located in the northern region of Brazil along the Transamazônica highway in the southwest of the state of Pará, has a large rural extension, with side roads without asphalt pavement and difficult access. In this work we will try to answer the following question: what are the main challenges faced by teachers of rural education in the rural modular system of schools in the municipality of Medicilândia-PÁ? This article aims to identify what form of higher education is offered in rural schools, and the main challenges faced by teachers of Rural Education in the modular system of fundamental education in schools in the municipality of Medicilândia. The specific objectives are: To understand the logistics of the science teacher who works with the rural modular system of fundamental education; analyze if there is pedagogical support and support to the teacher in the rural modular system of fundamental education; to characterize aspects that interfere in the work of the science teacher. The field research was carried out through a semi-structured questionnaire with semi-structured questions that guided the interview, which has quantitative and qualitative characteristics, with two different questionnaires, directed to 05 science teachers of elementary education who work in municipal schools, in classes of the system. modular elementary school education. The classes of the modular elementary school system are attached to an urban headquarters school and the classes are formed in rural schools distributed along the vicinal areas of the municipality. The modular system of basic education now presented has great social relevance for young people in the countryside of this municipality. Given the reports presented by teachers, it can be observed that there are many challenges faced by them. Among so many challenges, it was identified that no teacher who works in science classes has a specific higher education in the science area and still works teaching multiple disciplines.